Smart agricultural services using deep learning, big data, and IoT - Gupta, Amit Kumar 1981-; Goyal, Dinesh 1976-; Singh, Vijendra; Sharma, Harish (IGI Global, 2021)
"This book explores the application of deep learning, big data, IoT in agricultural services"--
Includes bibliographical references and index. - Description based on title screen (IGI Global, viewed 10/24/2020)
Keywords: Agricultural informatics; Artificial intelligence; Agricultural applications; Internet of things; Machine learning; Big data; Agricultural informatics; fast; Artificial intelligence; Agricultural applications; fast; Big data; fast; Internet of things; fast; Machine learning; fast